Keeping the door open: romantic science and the experience of self - Halliwell, Martin (1996)
The thesis positions three modem thinkers working in different areas of the human sciences - William James, Ludwig Binswanger and Oliver Sacks - within a framework of romantic science. Romantic science is a term which is developed explicitly in the work of Sacks and also illuminates the central concerns of James and Binswanger. As such, romantic science provides a useful framework in which to discuss conceptual changes in the medical humanities (a branch of the human sciences directed to patient care) since the late nineteenth century.